140k views
4 votes
Solve the system of equations using substitution. Write the solution as an ordered pair.

y = x + 6
y = –2x – 3

1 Answer

2 votes

Answer:

(-3, 3)

Explanation:

Substitute for y:

x+6 = -2x -3

3x = -9 . . . . . . . add 2x -6 to both sides

x = -3 . . . . . . . . divide by 3

y = (-3) +6 = 3 . . substitute for x in the first equation

The solution is ...

(x, y) = (-3, 3)

Solve the system of equations using substitution. Write the solution as an ordered-example-1
User Lonegunman
by
6.0k points